Opting for an open society?: Personality traits and attitudes toward the openness of Switzerland - Ackermann, Kathrin; Ackermann, Maya; Freitag, Markus (Comparative European politics, 2018)
The tension between openness and closedness is one of the most important cleavages in Swiss political debates. In the present article, we study the psychological foundations of attitudes regarding this issue. More precisely, we examine the link between personality and attitudes toward the degree of openness of Switzerland as a general stance toward the cultural, economic and political alignment of the country. Personality is understood as a complex and multifaceted concept that forms the basis for consistent patterns of attitudes and behavior. We build on the Five-Factor Theory to explain the link between personality traits, contextual factors and political attitudes. Analyzing survey data from a random sample of Swiss citizens, we find clear evidence that personality traits affect political attitudes. Furthermore, we are able to demonstrate that the relationship between personality and attitudes toward the degree of openness of Switzerland is moderated by perceived ethnic diversity in the neighborhood.
Gesehen am 14.04.2021